Rethinking the Constitutional Criminal Procedure of Juvenile Transfer Hearings: Apprendi, Adult Punishment, and Adult Process - Carroll, Jenny E. (2009)
This Article makes valuable new contributions to the burgeoning scholarly discourse on Apprendi v. New Jersey-a landmark decision that celebrates its tenth anniversary this year. It builds on the Author's experience as a public defender, during which she pioneered the surprising but straightforward argument that under Apprendi, findings that justify transferring a juvenile to adult court must be proven to a jury beyond a reasonable doubt. Apprendi requires that any fact authorizing a sentence higher than the otherwise applicable statutory maximum must be found by a jury using a beyond a reasonable doubt standard. This tenet applies directly to juvenile transfer hearings, which rely on a consideration of facts to determine whether a juvenile should face trial and sentence in adult court. The facts that serve as a basis for transfer result in exposure to a higher sentence than could be imposed if the offender remained in juvenile court. Despite Apprendi's readily apparent application, juvenile courts have refused to apply Apprendi to juvenile transfer hearings. This Article presents this argument and critiques the reasoning of courts that have refused to apply Apprendi in this context. It then explores the theoretical underpinnings of courts' reluctance to apply Apprendi, filling a scholarly void that exists at the intersection of Apprendi and the juvenile justice system